SphereZyme (TM) technology for enhanced enzyme immobilisation application in biosensors - Molawa, Letshego Gloria (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
Self-immobilisation enzyme technologies, such as SphereZyme™, suffer from the lack of applicability to hydrolyse large substrates. Solid support immobilisation is usually a method of choice, to produce a stable biocatalyst for large substrates hydrolysis in the industry. In order to investigate this limitation, a commercial protease called Alcalase® was chosen as a model enzyme due to its natural activity (hydrolysis of large substrates-proteins). Prior to immobilising through the SphereZyme™ technology, Alcalase® was partially purified through dialysis followed by CM Sepharose™ FF cation exchanger. Sample contaminants, such as salts and stabilisers can inhibit protein crosslinking by reacting with glutaraldehyde. Alcalase® was successfully separated into 3 proteases with the major peak correlating to a positive control run on native PAGE, indicating that it was likely subtilisin Carlsberg. A 16% alkaline protease activity for azo-casein hydrolysis was retained when 5% v/v PEI: 25% v/v glutaraldehyde solution was used as a crosslinking agent in Alcalase® SphereZyme™ production. An increase in activity was also observed for monomeric substrates (PNPA) where the highest was 55%. The highest % activities maintained when 0.33 M EDA: 25% v/v glutaraldehyde solution was initially used as crosslinking agent were 4.5% and 1.6% for monomeric and polymeric substrates, respectively. PEI is a hydrophilic branched polymer with an abundance of amine groups compared to EDA. A comparison study of immobilisation efficiencies of SphereZyme™, Eupergit® and Dendrispheres was also performed for large substrate biocatalysis. The two latter technologies are solid-support immobilisation methods. Dendrispheres reached its maximum loading capacity in the first 5 minute of the one hour binding time. Twenty minutes was chosen as a maximum binding time since there was constant protein maintained on the solid support and no enzyme loss was observed during the 1 hour binding time. PEI at pH 11.5, its native pH, gave the highest immobilisation yield and specific activity over the PEI pH range of 11.5 to 7. SphereZyme™ had the highest ratio for azocasein hydrolysis followed by Dendrispheres and Eupergit®. The SphereZyme™ was also shown to be applicable to biosensors for phenol detection. Different modifications of glassy carbon electrode (GCE) were evaluated as a benchmark for the fabrication of SphereZyme™ modified phenol biosensor. GCE modified with laccase SphereZyme™ entrapped in cellulose membrane was the best modification due to the broad catechol range (<0.950 mM), high correlation coefficient (R2, 0.995) and relative high sensitivity factor (0.305 μA.mM-1). This type of biosensor was also shown to be electroactive at pH 7.0 for which its control, free laccase, lacked electroactivity. From the catalytic constants calculated, GCE modified with laccase SphereZyme™ entrapped in cellulose membrane also gave the highest effectiveness factor (Imax/Km app) of 1.84 μA.mM-1. The modified GCE with Alcalase® SphereZyme™ was relatively more sensitive than GCE modified with free Alcalase®.
Keywords: Immobilized enzymes; Hydrolases; Hydrolysis; SphereZyme; Biosensors; Proteolytic enzymes